A Dynamin Homolog Promotes the Transition from Hemifusion to Content Mixing in Intracellular Membrane Fusion. (25th February 2014) - Kulkarni, Aditya; Alpadi, Kannan; Sirupangi, Tirupataiah; Peters, Christopher
<x xml:space="preserve">Abstract</x> Dynamin family members have been implicated in exocytosis. Vps1 (the yeast dynamin homolog) mutant vacuoles show decreased fusion and trans‐Soluble N‐ethylmaleimide sensitive factor Attachment Protein Receptor (SNARE) complex formation but comparable hemifusion relative to wild type. Vps1, through its oligomerization and SNARE‐domain binding, brings together multiple t‐SNAREs. This finding uncovers a novel function of Vps1 in coordinating the hemifusion – content mixing transition in yeast vacuole fusion.<boxed-text content-type="graphic" id="tra12156-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>